PUBLIC SPACE REPRESENTATION OF RAMAYANA SHENDRATARI OPEN STAGE AT PRAMBANAN TEMPLE IN THE THEORY PRODUCTION OF SPACE - Atmadi, Tunjung; Adnyana, I Wayan (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Prambanan Temple is a place of worship and also a tourist spot for activities for local visitors and foreign tourists, and can be visited every day from morning to evening. While the Prambanan Ramayana ballet is a performance that combines dance and drama without dialogue, taken from the Ramayana story.This study aims to describe the representation of space produced according to the spatial and social context in the perspective of the theory of Space Production, namely by feeling, understanding, and experiencing the existing space perceived space-conceived space-lived space. This study uses a descriptive qualitative method, namely the collection of primary data sources and secondary data. Data collection techniques are carried out using observation, interview and documentation methods. Data analysis techniques used are data reduction, data presentation and drawing conclusions. From the presentation that has been delivered, Henry Lefebvre's argument is considered to be able to provide a solution to the problem of social space production in Prambanan Temple. Three spatial characters (dimensions of spatial practice, spatial representation and representational space) are expected as a study that can unravel the problem of social space construction activities in the public space of the open stage of the Ramayana Ballet of Prambanan Temple.